HUBUNGAN PAPARAN DEBU DAN KARAKTERISTIK PEKERJA TERHADAP KAPASITAS VITAL PAKSA DAN VOLUME EKSPIRASI PAKSA DETIK PERTAMA PEKERJA PABRIK BAGIAN PENGOLAHAN PTPN XIII RIMBA BELIAN KABUPATEN SANGGAU - ., Grace Sheila Lames (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Industrial workers are exposed to physical, chemical, toxic andother factors that can lead to lung diseases. Dust polluted air exposure in theworkplace if mixed with dust will be inhaled and some will be accumulated in thelung, resulting in pulmonary disorders among factory workers. Objective: Theaim of this study is to know the relationship between dust exposure and workerâ€™scharacteristic with FVC and FEV. Method: This research was an analytic studywith a cross-sectional approach and using non-probability sampling (purposivesampling) technique. 26 workers were interviewed using questionnaire, the FVCand FEV11 were determined by spirometry, the datas were analyzed using Fishertest. Result: 21 workers had normal lung functions based on FVC and FEV. Mostof the workers were on low dust exposure (69,3%), length of workÂ <10 year(50%), normal nutritional status (42,3%), never used of masks (100%) and lightsmoker (53,85%). There was no relationship between dust exposure, nutritionalstatus, and smoking habitsÂ with FVC and FEV11(p=0,236; p=0,356; p=0,236).There was a significant relationship between the length of work with FVC andFEV(p=0,039). Conclusion: Most of the workers have normal lung functionbased on spirometry measurement (80,77%). Kernel area has the highest dustexposure while boiler area has the lowest. There is a significant relationshipbetween the length of work with FVC and FEV1 . Keywords: Dust exposure, workers characteristic, FVC and FEV1.1) Medical School, Faculty of Medicine, Universitas Tanjungpura, Pontianak, 1West Kalimantan2) Department of Community Medicine, Faculty of Medicine, Universitas Tanjungpura, Pontianak, West Kalimantan3) Department of Physiology, Faculty of Medicine, Universitas Tanjungpura, Pontianak, West Kalimantan